Du problème de la description lexicographique des dénominations chromatiques - Krylosova, Svetlana; Tomachpolski, Valentin (Neophilologica, 2016)
The purpose of this research is to clarify concepts of basic color terms, semantic class of color vocabulary and their classification according to the principle of derivation. The study is mainly centered on the ways color terms are perceived and described, especially on problems related to their lexicographic definition. The initial phase involves the study of methods to determine color terms in monolingual dictionaries. At the final phase, the Authors discuss the idea of a special description which is crucial for color lexicon as a language subsystem, for which five models of lexicographic definition are considered.